Preparation method of composite super-hydrophilic self-cleaning coating with down-conversion and high light transmittance and photovoltaic module

By introducing Cs2ZrCl6 nanocrystals into the photovoltaic module coating, the downconversion of ultraviolet rays and the improvement of light energy utilization is achieved, and the problem that the existing photovoltaic module coating cannot resist ultraviolet rays and improve the light energy utilization is solved, which significantly improves the photovoltaic module. performance.

CN119430683APending Publication Date: 2025-02-14ELECTRIC POWER RES INST CHINA SOUTHERN POWER GRID CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411645579.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing photovoltaic module coatings cannot effectively resist ultraviolet radiation and improve the utilization of light energy, resulting in a degradation in the performance of photovoltaic modules.

Method used

Using a composite ultra-hydrophilic self-cleaning coating, the photovoltaic module's utilization of the full spectrum of the solar spectrum is improved by introducing the downconversion material Cs2ZrCl6 nanocrystals into the coating.

Benefits of technology

Effectively reduce the damage to photovoltaic modules by ultraviolet rays, improve the comprehensive power generation performance and long-term stability of photovoltaic modules, while maintaining high light transmittance and good self-cleaning performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430683A_ABST
    Figure CN119430683A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional coatings, and particularly discloses a preparation method of a composite super-hydrophilic self-cleaning coating with down-conversion and high light transmittance and a photovoltaic module. The preparation method of the composite super-hydrophilic self-cleaning coating with the down-conversion and high light transmittance comprises the following steps: sequentially preparing F, E and P solutions, etching a glass substrate with a mixed solution of concentrated sulfuric acid and hydrogen peroxide, sequentially immersing the glass substrate into the F, E and P solutions, and respectively calcining and drying after each coating to finally obtain the composite super-hydrophilic self-cleaning coating. The composite super-hydrophilic self-cleaning coating prepared by adopting the scheme of the invention can effectively capture ultraviolet light components in a solar spectrum and convert the absorbed ultraviolet light into visible light, so that the utilization rate of the photovoltaic module on the full spectrum of the sun is greatly improved, the comprehensive power generation performance of the photovoltaic module is improved, and the photovoltaic module has a wide application prospect. And moreover, the negative influence on the light transmittance and hydrophilicity is avoided, and the problem of low ultraviolet light utilization efficiency of the existing coating is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional coatings, and in particular to a preparation method of a composite super-hydrophilic self-cleaning coating with down-conversion and high light transmittance and a photovoltaic module. Background Art

[0002] In the vast field of renewable energy, photovoltaic technology has become the key to the transformation of the global energy structure due to its clean, pollution-free and efficient energy conversion characteristics. However, in actual application scenarios, photovoltaic modules must not only efficiently convert solar energy into electrical energy, but also maintain excellent performance in complex, changeable and harsh natural environments. Among them, high-intensity ultraviolet radiation and fogging are two challenges that cannot be ignored. When fogging occurs, if the droplet size exceeds half of the shortest wavelength of visible light (380nm), it will cause significant scattering of light and a significant decrease in transmittance, which will inevitably affect the power generation efficiency of photovoltaic modules.

[0003] The super-hydrophilic coating has a unique porous structure, which gives the coating excellent hydrophilicity. Thanks to this property, when water vapor contacts the surface of the coating, it does not condense into small water droplets, but forms a continuous and uniform water film. In this way, fog cannot be generated and the coating can maintain a high light transmittance. When rain or dew falls on the coating, they can quickly spread on the surface and penetrate under the stains attached to the surface of the photovoltaic module, and then easily wash away the stains, so that the surface of the photovoltaic module is always kept highly clean. However, although the existing coating technology can already realize the self-cleaning function of the surface of photovoltaic modules, it is still insufficient in providing additional protection for photovoltaic modules and improving their performance.

[0004] Ultraviolet radiation is the main cause of accelerated aging of photovoltaic materials. Currently, research progress in coatings to resist ultraviolet radiation or effectively utilize this light source is relatively limited. If down-conversion materials can be introduced into the coating, ultraviolet rays can be effectively captured and converted into energy in the visible light band. This process can not only reduce the direct damage of ultraviolet rays to photovoltaic modules, but also broaden the response range of the modules to the solar spectrum, especially enhance the utilization of low-energy visible light, thereby improving the comprehensive power generation efficiency and long-term stability of photovoltaic modules. Summary of the invention

[0005] In view of this, the present application aims to provide a preparation method of a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance and a photovoltaic module. The coating can convert light energy into other forms of energy, improve the spectrum utilization rate, and reduce the device degradation problem caused by ultraviolet rays, thereby solving the problem that the existing coating cannot resist ultraviolet rays and has low light energy utilization rate.

[0006] In order to achieve the above technical objectives, the present application provides a method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance, comprising the following steps:

[0007] Step S1, prepare liquid E, liquid F, and liquid P respectively:

[0008] Liquid A: Evenly mix TEOS, hydrochloric acid, deionized water and anhydrous ethanol to obtain Liquid A;

[0009] Liquid E: Mix ammonia water and anhydrous ethanol evenly to obtain liquid B; mix TEOS and anhydrous ethanol evenly to obtain liquid C; start stirring, add liquid C dropwise into liquid B, mix evenly to obtain liquid D; adjust the pH of liquid D to 7±0.2, mix liquid D and liquid A evenly to obtain liquid E;

[0010] Liquid F: Add PEG to liquid A and stir evenly to obtain liquid F;

[0011] P solution: Take Zr(CO3)2 and octadecene and place them in a flask and heat until a clear and transparent solution is formed; then add cesium oleate, oleic acid and oleylamine into the flask, then heat to 120-150°C, and evacuate the flask to remove residual octadecene; after the evacuation, introduce N2 gas into the flask and continue heating; when the temperature reaches 180-200°C, quickly inject TMSCl into the flask, and then cool it in an ice-water bath to obtain a crude solution; the crude solution is centrifuged to separate the solid part to obtain Cs2ZrCl6 nanocrystals; finally, take the Cs2ZrCl6 nanocrystals and disperse them in n-hexane to obtain P solution;

[0012] Step S2, preparation of coating:

[0013] Step S2-1, etching: immersing the glass substrate in a mixed solution of concentrated sulfuric acid and hydrogen peroxide for etching;

[0014] Step S2-2, first coating: immersing the etched glass substrate in liquid F, and using a dip coater to evenly coat the liquid F on the surface of the glass substrate, and performing a calcination operation after coating to obtain a first coating;

[0015] Step S2-3, second coating: after the first coating is cooled to room temperature, the first coating is immersed in liquid E, and liquid E is evenly coated on the surface of the first coating by a dip coater, and after coating, drying is performed to obtain a second coating;

[0016] Step S2-4, third coating: wait for the second coating to cool to room temperature, immerse the second coating in P liquid, and use a dip coater to evenly coat the P liquid on the surface of the second coating. After coating, dry it to obtain a composite transparent super hydrophilic self-cleaning coating.

[0017] Furthermore, in the P solution, the mass concentration of Cs2ZrCl6 nanocrystals is 15~20mg / mL.

[0018] Furthermore, in the P solution, the mass concentration of Cs2ZrCl6 nanocrystals is 15 mg / mL.

[0019] Furthermore, in step S1, the dosage ratio of TEOS, hydrochloric acid, deionized water and anhydrous ethanol is (5-5.5) mL: (0.3-0.5) g: (2-6) mL: (40-60) mL; the volume ratio of ammonia water to anhydrous ethanol is (7-10): (120-150); the volume ratio of TEOS to anhydrous ethanol is (10-15): (50-80); the volume ratio of D liquid and A liquid in E liquid is (40-70): (3-5); the dosage ratio of PEG and A liquid in F liquid is (0.2-0.5) g: (50-60) mL; the mass ratio of octadecene and Zr(CO3)2 is (18-19): (0.8-1); the mass ratio of cesium oleate, oleic acid and oleylamine is (0.9-1): (15-18): (4-8); in step S2, the volume ratio of concentrated sulfuric acid and hydrogen peroxide is 3:1.

[0020] Furthermore, in step S1, the components for preparing the P solution also include acetic acid; wherein the mass ratio of octadecene to acetic acid is (20-25):1; the preparation steps of the P solution are as follows: Zr(CO3)2, octadecene, and acetic acid are placed in a flask and heated until a clear and transparent solution is formed; cesium oleate, oleic acid, and oleylamine are added to the flask, and then the flask is heated to 120-150°C, and the flask is vacuumed to remove residual octadecene; after the vacuuming operation is completed, N2 gas is introduced into the flask and the heating is continued; when the temperature reaches 180-200°C, TMSCl is quickly injected into the flask, and then cooled in an ice-water bath to obtain a crude solution; the crude solution is centrifuged to obtain the solid part to obtain Cs2ZrCl6 nanocrystals; finally, the Cs2ZrCl6 nanocrystals are dispersed in n-hexane to obtain the P solution.

[0021] Furthermore, in step S1, the average molecular weight of PEG is 2000.

[0022] Furthermore, in step S2, the dipping rate is 1000-1500 μm / s.

[0023] Furthermore, in step S2-1, the etching time is 1.5 hours.

[0024] Furthermore, in step S2-2, the calcination temperature is 100-250° C., and the calcination time is 1-3 hours.

[0025] Furthermore, in step S2-3 and step S2-4, the drying temperature is 120-150° C., and the drying time is 1-1.5 h.

[0026] Secondly, the present application also provides a photovoltaic module, the surface of which is provided with a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance obtained by the above-mentioned preparation method.

[0027] In summary, the present application provides a method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance, by sequentially configuring F, E, and P liquids, and then etching the glass substrate with a mixture of concentrated sulfuric acid and hydrogen peroxide, and then immersing it in F, E, and P liquids in turn, and performing calcination and drying operations after each coating to obtain a composite super-hydrophilic self-cleaning coating. The composite super-hydrophilic self-cleaning coating prepared by the present application scheme can effectively capture the ultraviolet light component in the solar spectrum, convert the absorbed ultraviolet light into visible light, greatly improve the utilization rate of the photovoltaic module for the full solar spectrum, and improve the comprehensive power generation performance of the photovoltaic module; at the same time, the coating also has good hydrophilicity and can efficiently achieve self-cleaning. Compared with the prior art, the composite super-hydrophilic self-cleaning coating provided by the present application can capture ultraviolet light in the solar spectrum and absorb and convert it into visible light, has a down-conversion function, can improve the efficiency of light energy utilization, and will not have a negative impact on transmittance and hydrophilicity. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0029] Figure 1 This is a contact angle test diagram of the composite transparent super-hydrophilic self-cleaning coating provided in Example 1 of the present application;

[0030] Figure 2 This is a contact angle test diagram of the composite transparent super-hydrophilic self-cleaning coating provided in Example 2 of the present application;

[0031] Figure 3 The ultraviolet-visible light absorption characteristics and fluorescence emission characteristics spectrum provided in Example 2 of the present application;

[0032] Figure 4 This is a transmittance curve diagram of the composite transparent super hydrophilic self-cleaning coating prepared in Example 2, Example 3, and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0033] The technical solutions of the embodiments of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the specification of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection requested by the present application.

[0034] The sources of all raw materials in the present invention are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0035] The present invention provides a method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance, comprising the following steps:

[0036] Step S1, prepare liquid E, liquid F, and liquid P respectively:

[0037] Liquid A: Evenly mix TEOS, hydrochloric acid, deionized water and anhydrous ethanol to obtain Liquid A;

[0038] Liquid E: Mix ammonia water and anhydrous ethanol evenly to obtain liquid B; mix TEOS and anhydrous ethanol evenly to obtain liquid C; start stirring, add liquid C dropwise into liquid B, mix evenly to obtain liquid D; adjust the pH of liquid D to 7±0.2, mix liquid D and liquid A evenly to obtain liquid E;

[0039] Liquid F: Add PEG to liquid A and stir evenly to obtain liquid F;

[0040] P solution: Take Zr(CO3)2 and octadecene and place them in a flask and heat until a clear and transparent solution is formed; then add cesium oleate, oleic acid and oleylamine into the flask, then heat to 120-150°C, and evacuate the flask to remove residual octadecene; after the evacuation, introduce N2 gas into the flask and continue heating; when the temperature reaches 180-200°C, quickly inject TMSCl into the flask, and then cool it in an ice-water bath to obtain a crude solution; the crude solution is centrifuged to separate the solid part to obtain Cs2ZrCl6 nanocrystals; finally, take the Cs2ZrCl6 nanocrystals and disperse them in n-hexane to obtain P solution;

[0041] Step S2, preparation of coating:

[0042] Step S2-1, etching: immersing the glass substrate in a mixed solution of concentrated sulfuric acid and hydrogen peroxide for etching;

[0043] Step S2-2, first coating: immersing the etched glass substrate in liquid F, and using a dip coater to evenly coat the liquid F on the surface of the glass substrate, and performing a calcination operation after coating to obtain a first coating;

[0044] Step S2-3, second coating: after the first coating is cooled to room temperature, the first coating is immersed in liquid E, and liquid E is evenly coated on the surface of the first coating by a dip coater, and after coating, drying is performed to obtain a second coating;

[0045] Step S2-4, third coating: wait for the second coating to cool to room temperature, immerse the second coating in P liquid, and use a dip coater to evenly coat the P liquid on the surface of the second coating. After coating, dry it to obtain a composite transparent super hydrophilic self-cleaning coating.

[0046] Specifically, the vacuuming time is 1 hour, which can remove the unreacted octadecene in the flask to prevent it from interfering with subsequent reactions.

[0047] Specifically, the injection volume of TMSCl is 250-400 μL, which is used to terminate the reaction.

[0048] Specifically, the rotation speed of centrifugal separation is 5000~7000r / min, and the duration is 8~10min.

[0049] It should be noted that before etching the glass substrate, the surface of the substrate can be cleaned with deionized water to remove impurities and contaminants on the surface; then the cleaned substrate is immersed in isopropyl alcohol for 5 minutes to further remove residual contaminants on the surface, providing a clean substrate for subsequent etching and coating preparation.

[0050] In some embodiments, the mass concentration of Cs2ZrCl6 nanocrystals in the P solution is 15-20 mg / mL.

[0051] Preferably, in the P solution, the mass concentration of Cs2ZrCl6 nanocrystals is 15 mg / mL.

[0052] It should be noted that if the concentration is too low, the effect of down-conversion in the coating may not be obvious; if the concentration is too high, it may cause nanocrystals to agglomerate in the coating, affecting the uniformity and transparency of the coating, and thus negatively affecting the optical properties and self-cleaning properties of the coating. When the mass concentration is 15 mg / mL, the comprehensive performance of the coating can be optimized.

[0053] In some embodiments, in step S1, the dosage ratio of TEOS, hydrochloric acid, deionized water and anhydrous ethanol is (5~5.5) mL: (0.3~0.5) g: (2~6) mL: (40~60) mL; the volume ratio of ammonia water to anhydrous ethanol is (7~10): (120~150); the volume ratio of TEOS to anhydrous ethanol is (10~15): (50~80); the volume ratio of D liquid and A liquid in E liquid is (40~70): (3~5); the dosage ratio of PEG and A liquid in F liquid is (0.2~0.5) g: (50~60) mL; the mass ratio of octadecene and Zr(CO3)2 is (18~19): (0.8~1); the mass ratio of cesium oleate, oleic acid and oleylamine is (0.9~1): (15~18): (4~8); in step S2, the volume ratio of concentrated sulfuric acid and hydrogen peroxide is 3:1.

[0054] Preferably, in step S1, the components for preparing the P solution also include acetic acid; wherein the mass ratio of octadecene to acetic acid is (20-25):1; the preparation steps of the P solution are as follows: Zr(CO3)2, octadecene, and acetic acid are placed in a flask and heated until a clear and transparent solution is formed; cesium oleate, oleic acid, and oleylamine are added to the flask, and then the flask is heated to 120-150°C, and the flask is vacuumed to remove residual octadecene; after the vacuuming operation is completed, N2 gas is introduced into the flask and heating is continued; when the temperature reaches 180-200°C, TMSCl is quickly injected into the flask, and then cooled in an ice-water bath to obtain a crude solution; the crude solution is centrifuged to obtain the solid part to obtain Cs2ZrCl6 nanocrystals; finally, the Cs2ZrCl6 nanocrystals are dispersed in n-hexane to obtain the P solution.

[0055] It should be noted that, in the preparation process of P liquid, acetic acid participates in the acid-base balance adjustment of the reaction system, and the acetic acid is subsequently removed by vacuuming to prevent reaction with other components (such as Zr(CO3)2, cesium oleate, etc.) to affect the growth of nanocrystals. In this embodiment, by adjusting the mass ratio of octadecene and acetic acid, the synthesis process of nanocrystals can be smoothly carried out, and nanocrystals with stable performance and uniform particle size can be obtained.

[0056] In some embodiments, in step S1, the average molecular weight of PEG is 2000.

[0057] It should be noted that if the molecular weight is too small, the solution may be too thin, making it difficult to form a continuous and uniform coating on the substrate during dip coating; while a large molecular weight may cause the solution viscosity to be too high, resulting in problems such as difficulty in coating and uneven coating thickness; PEG with an average molecular weight of 2000 helps the solution to adhere better to the glass substrate during dip coating, ensuring uniformity of coating.

[0058] In some embodiments, in step S2, the dipping rate is 1000-1500 μm / s.

[0059] It should be noted that if the dipping rate is too fast, the amount of solution attached to the substrate is insufficient, which may cause the coating to be too thin or uneven; if the dipping rate is too slow, the solution may accumulate on the substrate, causing flow marks, uneven thickness and other problems, affecting the quality and performance of the coating. A dipping rate within the range of 1000~1500µm / s can form a uniform coating on the glass substrate, avoiding problems such as uneven thickness or flow marks.

[0060] In some embodiments, in step S2-1, the etching time is 1.5 hours.

[0061] It should be noted that if the etching time is too short, a good etching effect may not be achieved, affecting the bonding strength between the coating and the substrate; if the etching time is too long, the substrate may be over-corroded, destroying the structural integrity of the substrate. Within the above etching time, the surface of the glass substrate can be fully micro-etched to remove impurities and contaminants while forming a suitable micro-roughness, which is beneficial to the adhesion of subsequent coatings.

[0062] In some embodiments, in step S2-2, the calcination temperature is 100-250° C., and the calcination time is 1-3 hours.

[0063] It should be noted that calcining within the above-mentioned temperature and time range can allow the components in the coating to fully undergo chemical reactions and physical changes, ensuring that the reaction is complete, while avoiding defects in the coating such as cracking due to too long calcination time.

[0064] In some embodiments, in step S2-3 and step S2-4, the drying temperature is 120-150° C., and the drying time is 1-1.5 h.

[0065] It should be noted that after the second and third coatings, drying at 120-150°C for 1-1.5 hours can effectively evaporate the solvent and moisture in the coating and solidify the coating; it can also avoid decomposition of coating components due to excessively high temperature or surface defects due to excessively rapid drying.

[0066] The applicant further provides the following reference specific embodiments to describe the present invention. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0067] Example 1

[0068] This embodiment provides a method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance, and the specific steps are as follows:

[0069] Step S1, preparation of solution:

[0070] Solution A: Mix 5.1 mL TEOS, 0.4 g hydrochloric acid, 2 mL deionized water and 50 mL anhydrous ethanol to obtain Solution A;

[0071] Solution B: Mix 8 mL of aqueous ammonia and 132 mL of anhydrous ethanol to form Solution B.

[0072] Solution C: Mix 13.4 mL of TEOS and 68 mL of anhydrous ethanol to obtain Solution C;

[0073] Liquid D: Start stirring and slowly drop Liquid C into Liquid B to obtain Liquid D.

[0074] Solution E: When the pH value of solution D is adjusted to 7, mix 60 mL of solution D with 4 mL of solution A to obtain solution E.

[0075] Liquid F: Add 0.32 g PEG to liquid A and stir at 500 r / min for 6 hours to obtain liquid F;

[0076] P solution: Take 0.3g Zr(CO3)2 and 7.9g octadecene, put them into a two-necked flask and heat them to 80℃ until a clear and transparent solution is formed in the flask; then add 0.14g cesium oleate, 2.5g oleic acid and 0.56g oleylamine into the flask, and then perform vacuum operation for 1h; after the vacuum operation is completed, introduce N2 gas into the two-necked flask; heat and raise the temperature, when the temperature is heated to 200℃, quickly inject 400μL TMSCl, and cool it in an ice water bath after 10 seconds to obtain a crude solution, centrifuge the crude solution at 7000r / min for 10 minutes, and take the solid to obtain Cs2ZrCl6 nanocrystals; take 150mg of Cs2ZrCl6 nanocrystals, add them to 10mL n-hexane, and disperse them by ultrasonic wave to obtain P solution.

[0077] Step S2, preparation of coating:

[0078] Step S2-1, etching: the glass substrate is cleaned with deionized water for 5 minutes to remove impurities and contaminants on the surface; then it is immersed in isopropyl alcohol for 5 minutes to further remove the remaining contaminants on the surface; then it is immersed in a mixed solution of concentrated sulfuric acid and hydrogen peroxide with a volume ratio of 3:1 for etching for 1.5 hours.

[0079] Step S2-2, first coating: then immerse the etched glass substrate in F liquid, and use a dip coater to evenly coat the F liquid on the surface of the substrate at a speed of 1400 μm / s, and then calcine the coated substrate in a muffle furnace at a temperature of 200° C. for 2 hours to obtain a first coating.

[0080] Step S2-3, second coating: cool the first coating to room temperature, immerse it in liquid E, and use a dip coater to evenly coat the liquid E on the surface of the first coating at a speed of 1400 μm / s, and then dry it in an oven at a temperature of 120°C for 1 hour to obtain a second coating.

[0081] Step S2-4, third coating: After the second coating is cooled to room temperature, it is immersed in 15 mg / mL P solution, and the P solution is evenly coated on the surface of the second coating at a speed of 1000 μm / s by a dip coater, and then dried in an oven at a temperature of 100°C for 1 hour. A composite transparent superhydrophilic self-cleaning coating is obtained.

[0082] Test: The contact angle test was performed on the composite transparent super-hydrophilic self-cleaning coating prepared in the above embodiment. The test results are shown in Figure 1 and Table 1.

[0083] Example 2

[0084] The difference from Example 1 is that the dosage of raw materials and reaction parameters are different, as follows:

[0085] This embodiment provides a method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance, and the specific steps are as follows:

[0086] Step S1, preparation of solution:

[0087] Solution A: Mix 5.3 mL TEOS, 0.4 g hydrochloric acid, 2 mL deionized water and 50 mL anhydrous ethanol to obtain Solution A;

[0088] Solution B: Mix 7.8 mL of aqueous ammonia and 132 mL of anhydrous ethanol to form Solution B.

[0089] Solution C: Mix 13.4 mL of TEOS and 66 mL of anhydrous ethanol to obtain Solution C;

[0090] Liquid D: Start stirring and slowly drop Liquid C into Liquid B to obtain Liquid D.

[0091] Solution E: When the pH value of solution D is adjusted to 7, mix 60 mL of solution D and 3.7 mL of solution A to obtain solution E.

[0092] Liquid F: Add 0.4 g PEG to liquid A and stir at 500 r / min for 6 hours to obtain liquid F;

[0093] P solution: Take 0.3g Zr(CO3)2 and 7.9g octadecene, put them into a two-necked flask and heat to 80℃ until a clear and transparent solution is formed in the flask; then add 0.14g cesium oleate, 2.5g oleic acid and 0.56g oleylamine into the flask, and then perform vacuum operation for 1h; after the vacuum operation is completed, introduce N2 gas into the two-necked flask; heat and raise the temperature, when the temperature is heated to 200℃, quickly inject 400μL TMSCl, and cool it in an ice water bath after 10 seconds to obtain a crude solution, and centrifuge the crude solution at 7000r / min for 10 minutes to separate the solid to obtain Cs2ZrCl6 nanocrystals; add 150mg of Cs2ZrCl6 nanocrystals into 10mL n-hexane and disperse it by ultrasonic wave to obtain P solution.

[0094] Step S2, preparation of coating:

[0095] Step S2-1, first, clean the glass substrate with deionized water for 5 minutes to remove impurities and contaminants on the surface; then immerse it in isopropyl alcohol for 5 minutes to further remove residual contaminants on the surface; then immerse it in a mixed solution of concentrated sulfuric acid and hydrogen peroxide in a volume ratio of 3:1 for etching for 1.5 hours.

[0096] Step S2-2, first coating: then immerse the etched glass substrate in F liquid, and use a dip coater to evenly coat the F liquid on the surface of the substrate at a speed of 1200 μm / s, and then calcine the coated substrate in a muffle furnace at a temperature of 200° C. for 3 hours to obtain a first coating.

[0097] Step S2-3, second coating: cool the first coating to room temperature, immerse it in liquid E, and use a dip coater to evenly coat the liquid E on the surface of the first coating at a speed of 1400 μm / s, then dry it in an oven at 120°C for 1 hour, and then apply the second coating.

[0098] Step S2-4, third coating: After the second coating is cooled to room temperature, it is immersed in 15 mg / mL P solution, and the P solution is evenly coated on the surface of the second coating at a speed of 1000 μm / s by a dip coater, and then dried in an oven at a temperature of 100°C for 1 hour. A composite transparent superhydrophilic self-cleaning coating is obtained.

[0099] Testing: The composite transparent super-hydrophilic self-cleaning coating prepared in the above embodiment was subjected to contact angle test, light transmittance test, and UV-visible light absorption test. The test results are shown in Figures 2~4 and Table 1.

[0100] Example 3

[0101] The difference from Example 2 is that the concentration of Cs2ZrCl6 nanocrystals is different, and the concentration of Cs2ZrCl6 nanocrystals in the P solution is 20 mg / mL.

[0102] Test: The transmittance of the composite transparent super-hydrophilic self-cleaning coating prepared in the above embodiment was tested. The test results are shown in Figure 4 and Table 1.

[0103] Comparative Example 1

[0104] The difference from Example 2 is that no P liquid is applied.

[0105] Test: The transmittance of the composite transparent super-hydrophilic self-cleaning coating prepared in the above embodiment was tested. The test results are shown in Figure 4 and Table 1.

[0106] Please refer to Table 1 for the test results of the above embodiments and comparative examples.

[0107] Table 1

[0108]

[0109] Note: The effects of the embodiments and comparative examples in Table 1 are shown in the attached Figures 1 to 4 .

[0110] The test results of the above embodiments and comparative examples are shown in Table 1 and the attached Figures 1 to 4 As can be seen from the figure, Figure 1 This is a contact angle test diagram of the composite transparent super-hydrophilic self-cleaning coating prepared in Example 1. The contact angle of the coating is 12.80°. Figure 2 This is a contact angle test diagram of the composite transparent super-hydrophilic self-cleaning coating prepared in Example 2. It can be seen from the figure that its contact angle is 6.51°. Figure 3 The UV-visible light absorption and fluorescence emission characteristics of the composite transparent super-hydrophilic self-cleaning coating prepared in Example 2 are shown in the graph. From the graph, the coating exhibits a strong absorption capacity in the ultraviolet region of 300-400nm; and at 450nm, the coating has a strong absorption capacity in the ultraviolet region of 300-400nm. The nanocrystals exhibit a sharp and high-intensity fluorescence emission peak. Figure 4 The light transmittances of Example 2 (see the red line), Example 3 (see the blue line) and Comparative Example 1 (see the black line) are respectively shown, and the light transmittances are 95.0%, 82.6% and 94.7%, respectively.

[0111] By comparing the data of Example 1 and Example 2, it can be found that the composite transparent super-hydrophilic self-cleaning coating prepared by Example 2 has a smaller contact angle by optimizing the film preparation process, which means that the coating has stronger hydrophilicity and its self-cleaning performance is also better. In addition, the composite transparent super-hydrophilic self-cleaning coating prepared in Example 2 shows strong absorption ability in the ultraviolet light region of 300~400nm. This characteristic fully demonstrates that the coating can effectively capture the ultraviolet light component in the solar spectrum; and at 450nm, the ultraviolet light in the coating is 0.1% and 0.2% respectively. The nanocrystals exhibited sharp and high-intensity fluorescence emission peaks, which confirmed that Nanocrystals can convert absorbed ultraviolet light into visible light. This conversion can improve the utilization rate of the photovoltaic module for the full spectrum of the sun, thereby improving the comprehensive power generation performance of the photovoltaic module. By comparing the transmittance data of Example 2, Example 3 and Comparative Example 1, it can be seen that when When the concentration of nanocrystal solution is 15 mg / mL, the light transmittance of the coating is the highest. The concentration of the nanocrystal solution is 15 mg / mL, and coating the solution on a substrate can not only improve the down-conversion efficiency of the coating, but also has no negative impact on the transmittance of the coating, and can even improve the transmittance.

[0112] The above are only preferred embodiments of the present application and are not intended to limit the present invention. Although the present application has been described in detail with reference to the examples, those skilled in the art can still modify the technical solutions recorded in the aforementioned examples or make equivalent substitutions for some of the technical features therein. However, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance, characterized in that: The following steps are involved: Step S1, prepare liquid E, liquid F, and liquid P respectively: Liquid A: Evenly mix TEOS, hydrochloric acid, deionized water and anhydrous ethanol to obtain Liquid A; Liquid E: Mix ammonia water and anhydrous ethanol evenly to obtain liquid B; mix TEOS and anhydrous ethanol evenly to obtain liquid C; start stirring, add liquid C dropwise into liquid B, mix evenly to obtain liquid D; adjust the pH of liquid D to 7±0.2, mix liquid D and liquid A evenly to obtain liquid E; Liquid F: Add PEG to liquid A and stir evenly to obtain liquid F; P solution: Take Zr(CO3)2 and octadecene and place them in a flask and heat until a clear and transparent solution is formed; then add cesium oleate, oleic acid and oleylamine into the flask, then heat to 120-150°C, and evacuate the flask to remove residual octadecene; after the evacuation, introduce N2 gas into the flask and continue heating; when the temperature reaches 180-200°C, quickly inject TMSCl into the flask, and then cool it in an ice-water bath to obtain a crude solution; the crude solution is centrifuged to separate the solid part to obtain Cs2ZrCl6 nanocrystals; finally, take the Cs2ZrCl6 nanocrystals and disperse them in n-hexane to obtain P solution; Step S2, preparation of coating: Step S2-1, etching: immersing the glass substrate in a mixed solution of concentrated sulfuric acid and hydrogen peroxide for etching; Step S2-2, first coating: immersing the etched glass substrate in liquid F, and using a dip coater to evenly coat the liquid F on the surface of the glass substrate, and performing a calcination operation after coating to obtain a first coating; Step S2-3, second coating: after the first coating is cooled to room temperature, the first coating is immersed in liquid E, and liquid E is evenly coated on the surface of the first coating by a dip coater, and after coating, drying is performed to obtain a second coating; Step S2-4, third coating: wait for the second coating to cool to room temperature, immerse the second coating in P liquid, and use a dip coater to evenly coat the P liquid on the surface of the second coating. After coating, dry it to obtain a composite transparent super hydrophilic self-cleaning coating.

2. The method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance according to claim 1, characterized in that: In the P solution, the mass concentration of Cs2ZrCl6 nanocrystals is 15 mg / mL.

3. The method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance according to claim 1, characterized in that: In the step S1, the dosage ratio of TEOS, hydrochloric acid, deionized water and anhydrous ethanol is (5-5.5) mL: (0.3-0.5) g: (2-6) mL: (40-60) mL; the volume ratio of ammonia water to anhydrous ethanol is (7-10): (120-150); the volume ratio of TEOS to anhydrous ethanol is (10-15): (50-80); the volume ratio of D liquid to A liquid in E liquid is (40-70): (3-5); the dosage ratio of PEG to A liquid in F liquid is (0.2-0.5) g: (50-60) mL; the mass ratio of octadecene to Zr(CO3)2 is (18-19): (0.8-1); the mass ratio of cesium oleate, oleic acid and oleylamine is (0.9-1): (15-18): (4-8); in step S2, the volume ratio of concentrated sulfuric acid to hydrogen peroxide is 3:

1.

4. The method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance according to claim 3, characterized in that: In the step S1, the components for preparing the P solution also include acetic acid; Among them, the mass ratio of octadecene and acetic acid is (20~25):1; The preparation steps of P solution are as follows: Zr(CO3)2, octadecene and acetic acid are placed in a flask and heated until a clear and transparent solution is formed; cesium oleate, oleic acid and oleylamine are added to the flask, and then heated to 120-150°C, and the flask is vacuumed to remove residual octadecene; after the vacuum operation is completed, N2 gas is introduced into the flask and heating is continued; when the temperature reaches 180-200°C, TMSCl is quickly injected into the flask, and then cooled in an ice-water bath to obtain a crude solution; the crude solution is centrifuged to obtain the solid part to obtain Cs2ZrCl6 nanocrystals; finally, the Cs2ZrCl6 nanocrystals are dispersed in n-hexane to obtain P solution.

5. The method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance according to claim 1, characterized in that: In step S1, the average molecular weight of PEG is 2000.

6. The method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance according to claim 1, characterized in that: In the step 2, the dipping rate is 1000-1500 μm / s.

7. The method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance according to claim 1, characterized in that: In the step S2-1, the etching time is 1.5 hours.

8. The method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance according to claim 1, characterized in that: In the step S2-2, the calcination temperature is 100-250° C., and the calcination time is 1-3 hours.

9. The method for preparing a composite super-hydrophilic self-cleaning coating with down-conversion and high transmittance according to claim 1, characterized in that: In the steps S2-3 and S2-4, the drying temperature is 120-150° C., and the drying time is 1-1.5 hours.

10. A photovoltaic module, characterized in that: The surface is provided with a composite super-hydrophilic self-cleaning coating with down-conversion and high light transmittance obtained by the preparation method according to any one of claims 1 to 9.